2009
DOI: 10.1002/ijc.24624
|View full text |Cite
|
Sign up to set email alerts
|

Serum olfactomedin 4 (GW112, hGC‐1) in combination with Reg IV is a highly sensitive biomarker for gastric cancer patients

Abstract: Gastric cancer (GC) is 1 of the most common human cancers. Early detection remains the most promising approach to improving long‐term survival of patients with GC. We previously performed Serial Analysis of Gene Expression (SAGE) on 4 primary GCs and identified several GC‐specific genes including Reg IV. Of these genes, olfactomedin 4 (OLFM4, also known as GW112 or hGC‐1) is a candidate gene for cancer‐specific expression. In this study, we examined the expression of olfactomedin 4 in human GC by immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
106
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 24 publications
10
106
2
Order By: Relevance
“…enhanced olfactomedin 4 expression has been reported in gastric cancer by northern blot analysis (7) and by immunostaining (8). Our previous immunohistochemical analysis revealed that olfactomedin 4 is expressed in 56% of gastric cancer tissues (9). in addition, olfactomedin 4 is a secreted protein, and we showed that serum olfactomedin 4 represents a novel biomarker for gastric cancer (9).…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…enhanced olfactomedin 4 expression has been reported in gastric cancer by northern blot analysis (7) and by immunostaining (8). Our previous immunohistochemical analysis revealed that olfactomedin 4 is expressed in 56% of gastric cancer tissues (9). in addition, olfactomedin 4 is a secreted protein, and we showed that serum olfactomedin 4 represents a novel biomarker for gastric cancer (9).…”
Section: Introductionsupporting
confidence: 61%
“…Our previous immunohistochemical analysis revealed that olfactomedin 4 is expressed in 56% of gastric cancer tissues (9). in addition, olfactomedin 4 is a secreted protein, and we showed that serum olfactomedin 4 represents a novel biomarker for gastric cancer (9). in crc patients, preoperative serum levels of olfactomedin 4 were increased in a small number of samples, and the sensitivities of serum olfactomedin 4 at stage i-iii were lower than those of cea (9).…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…The fact that the olfactomedins have been identified only in multicellular organisms suggests that they play a role in cell-cell interaction and signalling. Olfactomedins are involved in normal development and are associated with several diseases including open-angle glaucoma and cancer [18][19][20][21][22]. OLFM1 and 3 are expressed mainly in the brain, OLFM2 in the pancreas and prostate, and OLFM4 in the bone marrow, small intestine, colon and prostate [15].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, both OLFM1 and OLFM4 expression have been linked to early stage lung cancer, while OLFM4 expression has also been implicated in early stages of gastric, colon and breast cancer [19][20][21]. It may be that expression of OLFM3 in DLKP-SQ reflects an early stage cancer.…”
Section: Discussionmentioning
confidence: 99%